Heterogeneity of Bronchitis in Airway Diseases in Tertiary Care Clinical Practice - Liesel D’silva; Nesreen Hassan; Hong-Yu Wang; Melanie Kjarsgaard; Ann Efthimiadis; Frederick E Hargreave; Parameswaran Nair (Canadian Respiratory Journal)
BACKGROUND: Sputum cell counts have identified inflammatory subtypes of bronchitis in relatively small numbers of subjects with asthma, chronic obstructive pulmonary disease (COPD) and chronic cough in research studies. The prevalence of different subtypes of bronchitis in routine clinical practice, however, has not been reported.